Evaluating the Application of Occupational Health and Safety Management in Accordance with ISO 45001: 2018 in the Arabian Gulf Academy for Maritime Studies, based on the Standards of Performance Evaluation and Continuous Improvement: Evaluating the Application of Occupational Health and Safety Management in Accordance with ISO 45001: 2018 in the Arabian Gulf Academy for Maritime Studies, based on the Standards of Performance Evaluation and Continuous Improvement - Abbas, Alaa (The Gulf Economist, 2023)
The current research tries to determine the level of availability of the performance evaluation and continuous improvement requirements in the application of the ISO 45001:2018 Occupational Health and Safety Management System by depending on the qualitative design and by relying on the case study methodology for the purpose of evaluating and discussing the ISO45001: 2018 occupational health and safety system and standards. The study population was represented by departments and higher departments concerned with occupational safety and quality in the Arabian Gulf Academy for Maritime Studies. A checklist was built based on the specifications of the international standard (ISO 45001: 2018), as the sample included 12 individuals belonging to higher departments and departments concerned with occupational quality and safety. The research concluded that the application of the occupational health and safety management system in accordance with the international standard ISO 45001-2018 in the Arabian Gulf Academy for Maritime Studies is a basic and very important commitment, and the requirements for performance evaluation and improvement need significant developments to be at a level close to the international standard.